2021
DOI: 10.4174/astr.2021.100.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enhanced Recovery After Surgery program on hospital stay and 90-day readmission after pancreaticoduodenectomy: a single, tertiary center experience in Korea

Abstract: Purpose: Despite increasing number of reports on Enhanced Recovery After Surgery program (ERAS) and readmission after pancreaticoduodenectomy (PD) from Western countries, there are very few reports on this topic from Asian countries. This study aimed to evaluate the effects of ERAS on hospital stay and readmission and to identify reasons and risk factors for readmission after PD. Methods: This retrospective cohort study included 670 patients who underwent open PD from January 2003 to December 2017. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This may be attributed to the practice of "glocalization", which refers to simultaneous occurrence of both universalizing and particularizing tendencies in a contemporary system (97). Again, we noted a low representation of pre- (59,61,62,67,72,73,76,78,80,81,94,95) and intra-operative (59)(60)(61)(62)64,67,70,72,73,76,78,80,94,95) components in many of the institutional pathways. It is quite possible that some routine practices would not have been itemized as pathway components.…”
Section: Eras® In Pancreatic Surgerymentioning
confidence: 70%
See 1 more Smart Citation
“…This may be attributed to the practice of "glocalization", which refers to simultaneous occurrence of both universalizing and particularizing tendencies in a contemporary system (97). Again, we noted a low representation of pre- (59,61,62,67,72,73,76,78,80,81,94,95) and intra-operative (59)(60)(61)(62)64,67,70,72,73,76,78,80,94,95) components in many of the institutional pathways. It is quite possible that some routine practices would not have been itemized as pathway components.…”
Section: Eras® In Pancreatic Surgerymentioning
confidence: 70%
“…The search strategy identified 37 studies (https://cdn. amegroups.cn/static/public/cco-21-36-1.pdf) (85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96) published in the last 2 decades, including 4 RCTs (81,83,87,88). On comparing the components (pre-, intraand post-operative) of the pathways in these studies, we found considerable heterogeneity amongst institutional protocols.…”
Section: Eras® In Pancreatic Surgerymentioning
confidence: 97%
“…Additional-ly, one study was conducted in a foreign country and another did not include details about the ERAS protocol, leading to their exclusion. Finally, the remaining 16 studies were analyzed [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Table 1 presents the authorship status of anesthesiologists in these studies, along with the inclusion of ERAS items related to the field of anesthesiology.…”
Section: Current Status Of Eras In South Koreamentioning
confidence: 99%